(untitled) (Comprehensive Journal of Science, 2025)
Thiosulfate is recognized as a promising alternative lixiviant to cyanide for the extraction of gold from ore bodies. Gold thiosulfate ([Au(S2O3)2]3-), however, is not well-adsorbed by activated charcoal, making industrial scale use of thiosulfate for gold leaching impractical at present. Because of their high specific surface areas (500-1000 m2g-1) and uniform openframework nanoporosity (pore channel diameters in the range 3-10 nm), functionalized mesoporous silicas are widely recognized as highly effective materials for the selective, rapid and high capacity uptake of mercury, gold and platinum group ions. In the present work, the efficient and rapid adsorption of gold thiosulfate by thiol-functionalized mesoporous silica (hereafter designated MP-HMS) is demonstrated, whereby the thiol groups in the materials bind with the gold complexes by ligand displacement. The adsorbed gold could be leached out using cyanide, regenerating the adsorbent for further uptake cycles. Functionalized mesoporous silica is thus a promising candidate for the preconcentration of gold from thiosulfate leachate solutions.